Volumetric composition and hybridization effects on mechanical properties of the pultruded hybrid kenaf/glass fiber composites - Dizaji, Seyed Fariborz Hashemi (2015)
The properties of fiber reinforced composite materials strongly depend on the volumetric composition of the composite (i.e.,volume of fiber, matrix, and void). Natural fibers have lower packing ability than synthetic fibers. Thus, fiber volume fraction of natural fibers is less than that of synthetic fibers. This characteristic is very crucial particularly for controlling and designing the volumetric composition of the hybrid natural/synthetic fiber reinforced composites. Based on the constant local fiber volume fraction criteria, an equation was derived for calculation of the required number of yarn/roving for fabrication of pultruded hybrid kenaf/glass composites. Six types of pultruded composite (two non-hybrids and four hybrids) with different fiber mixing ratios were manufactured. The volumetric composition of the composites was determined gravimetrically. Optical microscopy was employed to determine the location of voids. Three types of voids were identified, namely lumen voids, interface voids and impregnation voids. It was found that there was a linear relationship (R2= 0.96) between the kenaf fiber and void volume fraction. Impregnation voids constituted the highest amount of the voids which appeared to be caused by the moisture content of the kenaf fibers. It was found that the volume fraction of the fiber is directly related to the selected number of rovings, and not affected by the void volume fraction of the composites. The experimental volumetric composition of the composites showed the very good agreement with the volumetric composition model. The hybridization effect was studied on interlaminar shear strength, compression, flexural, dynamic flexural vibration and damping properties of the composites. The failure modes under static loading condition were studied. It was found that the mechanical properties of the composites are decreased as the kenaf and void volume fraction is increased. The regression analysis showed that there is a good agreement between the static and dynamic flexural modulus.